FRI0714-HPR The patient's journey from onset of back pain to diagnosis of axial spondyloarthritis: results from a qualitative study. (12th June 2018) - Passalent, L.; Soever, L.; Bednis, K.; Hawke, C.; Bidos, A.; Bloom, J.; Rampersaud, Y.R.; Haroon, N.; Inman, R.
Abstract : Background: People with axial spondyloarthritis (SpA) wait an average of 9 years between onset of back pain and time to diagnosis by a rheumatologist (Feldkeller 2000). During this time, patients often experience significant pain and dysfunction, while waiting for appropriate diagnosis and intervention. Understanding patients' perspectives of this diagnostic process is essential in order to optimize early detection and promote appropriate management for axial SpA. Objectives: The purpose of this study was to understand patients' perspectives of referral and screening practices for axial SpA from onset of back pain to diagnosis by a rheumatologist. Methods: Semi-structured key informant interviews were conducted with patients diagnosed with axial SpA, based on ASAS criteria, attending a tertiary academic spondylitis clinic. Interviews addressed patients' experiences with screening and referral practices for adults with chronic back pain and suspected axial SpA from symptom onset to diagnosis. All interviews were recorded, transcribed verbatim and evaluated using a compare and contrast analysis by coding groups of words that addressed the research objectives. Two members of the research team undertook this exercise independently and then met to reconcile emergent overarching categories and their respective themes. NVIVO V9 was used to assist with organization of codes. Results: A total of 10 patient interviews were conducted. 90% of participants were male, mean age 42.8 years (± 12.6). The mean duration of back pain prior to diagnosis of axial SpA was 8.9 years (± 6.0). The majority of patients (90%) had post-secondary education. Three overarching categories were identified regarding patients' experiences with screening and referral practices for axial SpA from symptom onset to diagnosis and included: 1) "system factors"; 2) "healthcare provider factors" and 3) "patient factors". Themes related to "system factors" included timely and appropriate access to care. Perceived lack of clinical skills and healthcare provider interpersonal skills were allocated to the category of "healthcare provider factors". Themes identified under the category of "patient-related factors" included: coping with uncertainty; the role of health literacy; the notion of hope, and the belief of stoicism. Conclusions: The results of this study indicate that care provided by knowledgeable, caring, empathetic and receptive healthcare providers is critical to patients with axial SpA as they navigate the healthcare system from symptom onset to diagnosis. Furthermore, access to the right specialist, at the right time, in the right place may improve patients' experience of screening and referral practices for chronic back pain. Models of care and targeted patient and medical education strategies aimed at reducing the gap between onset of back pain and diagnosis of axial SpA may have the potential to improve existing screening and referral practices of axial SpA. Reference: 1. Feldkeller E, Bruckel J, Khan MA. Scientific contributions of ankylosing spondyolitis patient advocacy groups. Curr Opin Rheumatol2000;12:239–247. Disclosure of Interest: None declared